Synthesis and characterization of transparent superhydrophobic fluorinated graphene oxide and silica based sol gel coating films - Harun, Mohd Hamzah (2020)
Transparent water repellent organosilica based coating containing tetraorthosilicate (precursor), fluoroalkylsilane (hydrophobic agent) and nanofillers (roughness agent) were prepared by sol-gel method. The coating was prepared by modification of silica (SiO2) or graphene oxide (GO) nanofillers with siloxane having long chain fluoroalkylsilane that allow for reducing surface energy. Four different samples were prepared namely, tetraorthosilicate sol (TEOS sol), tetraorthosilicate-fluoroalkylsilane (TEOS-FAS), tetraorthosilicatefluoroalkylsilane- silica (TEOS-FAS-SiO2) and tetraorthosilicate-fluoroalkylsilanegraphene oxide (TEOS-FAS-GO). The hydrophobic coating solutions were prepared at different concentration percentages of silica and GO ranging from 0.04 pph - 0.20 pph respectively. The water contact angle, transmittance degree, surface morphology and topography, chemical composition and surface analysis were characterized by Attension Tensiometer, UV-Visible Spectrophotometer, Field Emission Scanning Electron Microscope (FESEM), Atomic Force Microscope (AFM), Fourier Transform Infrared Spectroscope (FTIR), and X-Ray Photoelectron Spectroscopy (XPS). The contact angle for TEOS sol formulation at different concentrations of tetraorthosilicate showed a hydrophilic behavior in which the contact angle measured was lower than 90o whereas for TEOS-FAS formulation, hydrophobic behavior was obtained in which the measured contact angles were between 90o and 115o. For TEOS-FAS-SiO2 and TEOS-FAS-GO, the contact angles obtained were in the range of pre-superhydrophobic and superhydrophobic range (120o - 168o). Such behavior can be explained by the presence of hydrophobic agents which were fluoroalkylsilane and nanosize fillers which were SiO2 and GO. To investigate the durability of hydrophobicity value, the contact angle after peeling test using Scotch tape was measured. It showed that the TEOS-FAS-GO is more durable as the drop of contact angle value is more gradual as compared with other samples. The transmittance for all samples showed that they were transparent and the range obtained was between 70% - 95%. FESEM images confirmed the presence of silica and GO in the samples in which for TEOS-FAS-SiO2, uniform structure was obtained whereas for TEOS-FAS-GO, it showed that the silica from TEOS grew onto the graphene flakes. FTIR showed that the most important peak at 1036-1055 cm-1 has been obtained which confirmed the covalent attachment of FAS with silanol particles within tetraorthosilicate matrix in TEOS-FAS-GO and TEOS-FAS-SiO2 formulation. AFM demonstrated that the roughness increased with the addition of silica and GO fillers with TEOS-FAS-GO gave relatively greater roughness than TEOS-FAS-SiO2 samples. XPS analysis showed that FAS and TEOS molecules were successfully grafted on the SiO2 and GO surfaces with hydroxyl and carboxyl groups were involved as well as silica nanoparticles from TEOS sol for TEOS-FAS-GO and silica nanoparticles itself for TEOS-FAS-SiO2. The introduction of SiO2 and GO in the formulation of transparent TEOS sol formulation containing long chain fluoroalkylsilane enhance the surface roughness and thus induces the hydrophobicity in which the water contact angle obtained in the range of hydrophobicity and superhydrophobicity (120o - 169o). This indicates that the surface roughness plays an important role in enhancing hydrophobicity and lowering the surface free energy. Although the transmittance degrees obtained were slightly lower than TEOS sol and TEOS-FAS formulation which were around 70-95%, the transmittance is still within the accepted level since the hydrophobic coatings obtained were visible.